1998
DOI: 10.1002/(sici)1097-4628(19980418)68:3<373::aid-app4>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Specific sorbents for bilirubin removal from human plasma: Congo red-modified poly(EGDMA/HEMA) microbeads

Abstract: Congo Red-modified poly(EGDMA-HEMA) microbeads were investigated as a specific sorbent for bilirubin removal from human plasma. Poly(EGDMA-HEMA) microbeads were prepared by a modified suspension copolymerization technique. Congo Red was covalently incorporated into the poly(EGDMA-HEMA) microbeads via condensation reactions between the aromatic amine groups of the dyes and the hydroxyl groups of the HEMA, under alkaline conditions. Bilirubin adsorption was investigated from hyperbilirubinemic human plasma on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Kanai et al have developed an improved model of anion exchange resin (IONEX) and they obtained the maximum amount of bilirubin in was 7.7 mg/g 35. Denizli et al used dye‐immobilised poly(hydroxyethyl methacrylate) microbeads and polyamide hollow fibres for bilirubin removal from human plasma 36–40. They obtained 6.8–48.9 mg per gram adsorbent.…”
Section: Resultsmentioning
confidence: 99%
“…Kanai et al have developed an improved model of anion exchange resin (IONEX) and they obtained the maximum amount of bilirubin in was 7.7 mg/g 35. Denizli et al used dye‐immobilised poly(hydroxyethyl methacrylate) microbeads and polyamide hollow fibres for bilirubin removal from human plasma 36–40. They obtained 6.8–48.9 mg per gram adsorbent.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the main aim is to provide a facile and convenient method to prepare practical particles for the removal of bilirubin. The adsorbed bilirubin amounts in this study were comparable to other reports [30][31][32].…”
Section: Effect Of Ligand Structure On Bilirubin Adsorptionmentioning
confidence: 99%
“…Polypeptide functionalized polyacrylamide beads prepared by Zhu et al were used as an affinity sorbent system for BR removal with adsorptions of 0.2-75 mg BR/g resin [10]. Denizli et al [21][22][23] have produced bioaffinity sorbents with poly(HEMA) or poly(EGDMA-HEMA) microbeads as basic carrier for bilirubin removal from aqueous media, including plasma, with a yield of 6.8-32.5 mg/g sorbent. Senel et al [25] reported that up to 48.9 mg BR were retained per gram of modified polyamide hollow fibers with Cibacron Blue F3GA attached as affinity ligand on the membrane surface.…”
Section: Static Bilirubin Adsorption Capacitymentioning
confidence: 99%
“…Under these, hemoperfusion, i.e., circulation of blood through an extracorporeal unit containing an adsorbent system for BR, has become the most promising technique [13][14][15][16][17][18][19][20][21][22][23][24][25]. In most cases basic ion exchange materials have been used, but uncharged polymers can also adsorb bilirubin from aqueous media.…”
Section: Introductionmentioning
confidence: 99%